ผลการเปลี่ยนแปลงอัตราการล้างย้อนต่อประสิทธิภาพของอัลตราฟิลเตรชันเมมเบรนต้นแบบในการผลิตน้ำประปา - ศักดิ์สิทธิ์ อิ่มแมน (จุฬาลงกรณ์มหาวิทยาลัย, 2008)
The purpose of this research is to study the effect of backwash rate on performance of prototype ultrafiltration membrane for water supply production, based on operating pressure, backwash rate, long-term operation and mathematical model to predict permeate flux, compared with the data from experimental. The experiment was conducted by using raw water from water supply canal at the Samsen. The prototype system was composed of three of membrane modules, raw water tank and clear water tank. In this research, operating pressure were varied to 100, 110, 120, 130, 140 and 150 kPa, and backwash rates were varied to 7, 4 and 2 m[superscript 3]/hr. From the results, the optimum operating pressure and backwash rate were 150 kPa and 7 m[superscript 3]/hr, respectively. The highest shear rate was found to be 1,607.14 Pa. Moreover mathematical model was developed to describe relationships between shear rate and total resistance. The model simulation could predict optimum backwash rate in order to prevent membrane fouling. Furthermore resistance-in-series model and pore model could predict permeate flux satisfactorily. Then, there mathematical models can be applied for this ultrafiltration membrane application.